Precursor-oriented CuCo2S4 counter electrode with different morphologies and preparation method and application thereof

CuCo2S4 materials with different morphologies were prepared through a precursor-guided strategy, which solved the problem of CuCo2S4 morphology control, improved the electrocatalytic performance and stability of QDSSCs, achieved high photoelectric conversion efficiency, and replaced complex precious metal systems.

CN120637111APending Publication Date: 2025-09-12SHANDONG PETROCHEMICAL INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510830853.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing technologies make it difficult to effectively regulate the morphology and structure of CuCo2S4 through simple methods, resulting in insufficient catalytic performance and stability in quantum dot-sensitized solar cells (QDSSCs), limiting the improvement of device performance.

Method used

A precursor-guided strategy was adopted to prepare CuCo2S4 with different morphologies, including nanoflowers, nanosheets, nanoparticles and nanospheres, through a solvothermal reaction method. The counter electrode was prepared by combining the screen printing method, which simplified the process and achieved controllable synthesis of the morphology.

Benefits of technology

The electrocatalytic performance of CuCo2S4 materials in QDSSCs has been significantly improved, with the photoelectric conversion efficiency increased by 24%–55%. It also exhibits excellent stability and catalytic performance in polysulfide electrolytes, replacing complex precious metal systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637111A_ABST
    Figure CN120637111A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of new energy and new materials, and relates to a precursor-oriented CuCo2S4 counter electrode with different morphologies and a preparation method and application thereof. According to the preparation method, a precursor guiding strategy is adopted, nano flower-shaped CuCo2S4, nano sheet-shaped CuCo2S4, nano particle-shaped CuCo2S4 and nano microsphere-shaped CuCo2S4 can be prepared through a simple solvothermal reaction method, the preparation method is simple and convenient, the morphology controllability is high, and a complex template agent is not needed. The prepared nanoflower-shaped CuCo2S4 shows the maximum specific surface area and charge transfer efficiency, the photoelectric conversion efficiency of a QDSSCs device corresponding to the nanoflower-shaped CuCo2S4 can reach 7.42% and is remarkably higher than the highest conversion efficiency of QDSSCs assembled by CuCo2S4 counter electrodes in other shapes and existing CdS / CdSe sensitized QDSSCs based on the CuCo2S4 counter electrodes, and the electro-catalytic performance is remarkably improved. The CuCo2S4 material prepared by the method is suitable for various electrolyte systems, shows excellent stability and catalytic performance in polysulfide electrolyte, and is expected to replace a complex noble metal system and a traditional binary Cu2S-based counter electrode system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy and new materials, and relates to a CuCo2S4 counter electrode material, and in particular to a precursor-guided CuCo2S4 counter electrode with different morphologies, and a preparation method and application thereof. Background Art

[0002] Quantum dot-sensitized solar cells (QDSSCs) have become a key research area in the solar cell field in recent years due to their broad spectral absorption, high theoretical efficiency, low cost, and flexible fabrication methods. The overall photoelectric conversion efficiency of QDSSCs depends not only on the performance of the quantum dot-sensitized photoanode but also on the catalytic activity and stability of the counter electrode (CE).

[0003] In a typical QDSSC device structure, the counter electrode, as the electron injection terminal, needs to have not only good conductivity but also high electrocatalytic activity to promote the redox couple in the electrolyte (such as S 2- / S n 2- Therefore, the development of counter electrode materials with stable structure, excellent catalytic performance and high interfacial reaction efficiency has always been the key to improving the performance of QDSSCs.

[0004] In recent years, multi-element transition metal sulfides have attracted increasing attention due to their unique multivalent metal ion synergistic effects and excellent electrical conductivity. Among them, spinel-type bimetallic sulfides (such as CuCo2S4 and NiCo2S4) have demonstrated excellent performance in electrochemical catalysis. While some studies have incorporated them into counter electrodes in QDSSCs, a systematic and in-depth study of the relationship between their microstructure and optoelectronic properties remains lacking.

[0005] In addition, existing studies have shown that the morphology and microstructure of catalytic materials have a significant impact on their charge transfer ability, specific surface area and electrolyte diffusion path. By regulating the morphology and structure of CuCo2S4, the exposure of its surface active sites and the efficiency of electron migration can be effectively improved, thereby optimizing the overall performance of the device. However, current research on the morphology regulation of CuCo2S4 mostly relies on templates, surfactants or complex structure directing agents. Not only is the process complicated, but it is also difficult to achieve a synergistic improvement in structural stability and catalytic performance, which limits its promotion and performance optimization in actual photovoltaic devices. Therefore, how to develop a simple, controllable and general strategy suitable for the synthesis of CuCo2S4 with different morphologies, achieve effective regulation of the material morphology, and improve its application performance in QDSSCs, is still a key technical problem that urgently needs to be broken through in this field. Summary of the Invention

[0006] In order to solve the above technical problems, the present invention provides a method for synthesizing CuCo2S4 with different morphologies using a precursor-guided strategy, and applies it to the counter electrode of QDSSCs, exploring the influence of CuCo2S4 counter electrodes with different morphologies on the photovoltaic performance of QDSSCs, so as to screen out the optimal morphology structure, laying the foundation for the subsequent preparation of CuCo2S4-based composite counter electrodes with further improved performance.

[0007] On the one hand, the present invention provides a precursor-guided method for preparing CuCo2S4 with different morphologies, which is prepared by a simple solvent thermal reaction method, comprising the following steps:

[0008] (1) Add a certain amount of copper salt to ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt salt and a certain amount of thiourea in sequence; wherein the acid radical ions of the copper salt and the cobalt salt are the same; and the molar ratio of copper ion, cobalt ion and thiourea is 1:(2-3):(5-6);

[0009] (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a reactor and heated to 160-180 °C for 10-12 h at a heating rate of 2 °C / min;

[0010] (3) After the above reaction is completed and cooled naturally to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain CuCo2S4 with a certain morphology.

[0011] Furthermore, the copper salt described in step (1) is one of copper chloride, copper nitrate, copper sulfate, copper acetate, copper chloride hydrate, copper nitrate hydrate, copper sulfate hydrate, and copper acetate hydrate, and the cobalt salt is one of cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt chloride hydrate, cobalt nitrate hydrate, cobalt sulfate hydrate, and cobalt acetate hydrate.

[0012] Furthermore, the stirring time in step (2) is more than 30 min.

[0013] Furthermore, the above method can prepare nano-flower-shaped CuCo2S4, nano-sheet-shaped CuCo2S4, nano-particle-shaped CuCo2S4 and nano-microsphere-shaped CuCo2S4.

[0014] Furthermore, the present invention provides a method for preparing nanoflower-shaped CuCo2S4, comprising the following steps:

[0015] (1) Add a certain amount of copper chloride or copper chloride hydrate to ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt chloride or cobalt chloride hydrate and a certain amount of thiourea in sequence; the molar ratio of the added copper ions, cobalt ions and thiourea is 1:(2-3):(5-6);

[0016] (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a reactor and heated to 160-180 °C for 10-12 h at a heating rate of 2 °C / min;

[0017] (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol, respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain nanoflower-like CuCo2S4 (f-CuCo2S4).

[0018] Furthermore, the present invention provides a method for preparing nano-sheet CuCo2S4, comprising the following steps:

[0019] (1) Add a certain amount of copper nitrate or copper nitrate hydrate to an ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt nitrate or cobalt nitrate hydrate and a certain amount of thiourea in sequence; the molar ratio of the added copper ion, cobalt ion and thiourea is 1:(2-3):(5-6);

[0020] (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a reactor and heated to 160-180 °C for 10-12 h at a heating rate of 2 °C / min;

[0021] (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol, respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain nanosheet-shaped CuCo2S4 (n-CuCo2S4).

[0022] Furthermore, the present invention provides a method for preparing nanoparticle-shaped CuCo2S4, comprising the following steps:

[0023] (1) Add a certain amount of copper sulfate or copper sulfate hydrate to ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt sulfate or cobalt sulfate hydrate and a certain amount of thiourea in sequence; the molar ratio of the added copper ions, cobalt ions and thiourea is 1:(2-3):(5-6);

[0024] (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a reactor and heated to 160-180 °C for 10-12 h at a heating rate of 2 °C / min;

[0025] (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol, respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain nanoparticles of CuCo2S4 (p-CuCo2S4).

[0026] Furthermore, the present invention provides a method for preparing nano-microspherical CuCo2S4, comprising the following steps:

[0027] (1) Add a certain amount of copper acetate or copper acetate hydrate to an ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt acetate or cobalt acetate hydrate and a certain amount of thiourea in sequence; the molar ratio of the added copper ions, cobalt ions and thiourea is 1:(2-3):(5-6);

[0028] (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a reactor and heated to 160-180 °C for 10-12 h at a heating rate of 2 °C / min;

[0029] (3) After the above reaction is completed and cooled to room temperature naturally, the resulting precipitate is washed several times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain nano-microspherical CuCo2S4 (m-CuCo2S4).

[0030] On the other hand, the nano-flower-like CuCo2S4, nano-sheet-like CuCo2S4, nano-particle-like CuCo2S4 and nano-microsphere-like CuCo2S4 prepared by the present invention can be used to prepare the counter electrode of the QDSSC device.

[0031] In another aspect, the present invention provides a method for preparing precursor-guided CuCo2S4 counter electrodes with different morphologies, comprising the following steps:

[0032] 1) CuCo2S4 powders of different morphologies prepared by the above method are mixed with a pore-forming agent and a binder in a mass ratio of 10:(1-2):(40-50), and the dispersant is added in a ratio of (0.1-0.2) g of CuCo2S4 powder to (5-10) mL of dispersant, and ground into a slurry; the pore-forming agent is preferably ethyl cellulose, the binder is preferably pine oil ethanol, and the dispersant is ethanol or n-butanol;

[0033] 2) The slurry was evenly coated on the pre-treated FTO conductive glass surface by screen printing;

[0034] 3) After pre-drying at 80 °C for 3-5 min and high-temperature annealing at 350-400 °C for 30-35 min, a dense and well-adhesive CuCo2S4 electrode film layer is formed.

[0035] Beneficial effects of the present invention:

[0036] The present invention achieves the controllable synthesis of CuCo2S4 with different morphologies through a precursor-guided strategy. The preparation method is simple and the morphology is highly controllable. No complex template is required. By simply adjusting the precursor type, the precise synthesis of CuCo2S4 with various morphologies, such as nanosheets, nanoflowers, nanospheres, and nanoparticles, can be achieved.

[0037] The nanoflower-like CuCo2S4 material (f-CuCo2S4) prepared by this invention exhibits the largest specific surface area and charge transfer efficiency. Its corresponding QDSSC device has a photoelectric conversion efficiency (PCE) of 7.42%, which is 24%–55% higher than the PCE of QDSSCs assembled with CuCo2S4 counter electrodes of other morphologies. It is also approximately 40% higher than the highest conversion efficiency (5.28%) of existing CdS / CdSe-sensitized QDSSCs based on CuCo2S4 counter electrodes, and its electrocatalytic performance is significantly improved. The CuCo2S4 material is suitable for a variety of electrolyte systems and exhibits excellent stability and catalytic performance in polysulfide electrolytes, making it a promising alternative to complex precious metal systems and traditional binary Cu2S-based counter electrode systems.

[0038] Through the above technical solution, the present invention not only realizes the preparation of CuCo2S4 materials with different morphological structures using a precursor-guided strategy, but also realizes the coordinated optimization of morphology control and electrochemical and photovoltaic performance, providing a new material system and process path for the subsequent further development of high-performance QDSSCs. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the X-ray photoelectron spectrum of f-CuCo2S4 of the present invention;

[0040] (a) XPS full spectrum; (b) Cu2p; (c) Co2p; (d) XPS high-resolution spectrum of S2p;

[0041] Figure 2 This is the SEM element scanning mapping of f-CuCo2S4 of the present invention;

[0042] Figure 3 This is the EDS spectrum of f-CuCo2S4 of the present invention;

[0043] Figure 4 TEM image of f-CuCo2S4 and SEM cross-sectional image of f-CuCo2S4 counter electrode of the present invention;

[0044] (a, b) TEM images of f-CuCo2S4; (c) high-resolution TEM image of f-CuCo2S4; (d) SEM cross-sectional image of the f-CuCo2S4 counter electrode; (eh) TEM elemental scanning mapping of f-CuCo2S4;

[0045] Figure 5 XRD patterns of CuCo2S4 with different morphologies of the present invention;

[0046] Figure 6 The SEM images of CuCo2S4 with different morphologies of the present invention are as follows;

[0047] (a) f-CuCo2S4; (b) n-CuCo2S4, (c) p-CuCo2S4, (d) m-CuCo2S4;

[0048] Figure 7 High-resolution SEM images of CuCo2S4 with different morphologies of the present invention;

[0049] (a) f-CuCo2S4; (b) n-CuCo2S4; (c) p-CuCo2S4; (d) m-CuCo2S4;

[0050] Figure 8 N2 adsorption isotherms of CuCo2S4 with different morphologies of the present invention;

[0051] Figure 9 This is a test diagram of the electrochemical performance of CuCo2S4 with different morphologies of the present invention;

[0052] (a) Nyquist plot (inset is an enlarged view); (b) Bode phase diagram (inset is an equivalent circuit diagram); (c) Tafel polarization curve; (d) linear sweep voltammetry (LSV) curve;

[0053] Figure 10 Schematic diagram of the working principle of QDSSCs;

[0054] Figure 11 The JV curves of QDSSCs based on CuCo2S4 counter electrodes with different morphologies of the present invention are shown;

[0055] Figure 12 1 is a cyclic voltammetry (CV) test curve of the counter electrodes with different morphologies in the three-electrode system of the present invention;

[0056] Figure 13 This is a graph showing continuous multi-cycle voltammetry tests of electrodes with different morphologies based on a symmetrical battery according to the present invention;

[0057] (a) f-CuCo2S4; (b) n-CuCo2S4; (c) p-CuCo2S4; (d) m-CuCo2S4;

[0058] Figure 14 The QDSSCs constructed with the counter electrodes of different morphologies in the present invention were -2 , open circuit voltage degradation (OCVD) curve under AM 1.5G conditions (a) and on-off experimental test curve (b);

[0059] Figure 15 Statistical histogram of the efficiency of QDSSCs constructed with electrodes of different morphologies in the present invention. DETAILED DESCRIPTION

[0060] Example 1

[0061] This embodiment provides a method for preparing nanoflower-shaped CuCo2S4, comprising the following steps:

[0062] (1) Add 0.5 mmol of copper chloride hydrate (CuCl2·2H2O) to 60 mL of ethylene glycol solution and stir until completely dissolved; then add 1 mmol of cobalt chloride hexahydrate (CoCl2·6H2O) and 3 mmol of thiourea in sequence;

[0063] (2) After continuous stirring for 30 min, the mixed solution was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 180 °C for 12 h at a heating rate of 2 °C / min;

[0064] (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed three times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 60 °C for 10 h to obtain nanoflower-like CuCo2S4 (f-CuCo2S4).

[0065] The X-ray photoelectron spectrum of f-CuCo2S4 is shown in Figure 1 As shown, the SEM element scanning map is as follows Figure 2 As shown, the EDS spectrum is as follows Figure 3 As shown in the TEM image Figure 4 shown.

[0066] Example 2

[0067] This embodiment provides a method for preparing nano-sheet CuCo2S4, comprising the following steps:

[0068] (1) Add 0.5 mmol of copper nitrate hydrate (Cu(NO3)2·3H2O) to 60 mL of ethylene glycol solution and stir until completely dissolved; then add 1 mmol of cobalt nitrate hydrate (Co(NO3)2·6H2O) and 3 mmol of thiourea in sequence;

[0069] (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a polytetrafluoroethylene reactor and reacted at 180 °C for 12 h at a heating rate of 2 °C / min;

[0070] (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed three times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 60 °C for 10 h to obtain nanosheet-shaped CuCo2S4 (n-CuCo2S4).

[0071] Example 3

[0072] This embodiment provides a method for preparing nanoparticle-shaped CuCo2S4, comprising the following steps:

[0073] (1) Add 0.5 mmol of copper sulfate hydrate (CuSO4·5H2O) to 60 mL of ethylene glycol solution and stir until completely dissolved; then add 1 mmol of cobalt sulfate hydrate (CoSO4·7H2O) and 3 mmol of thiourea in sequence;

[0074] (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a polytetrafluoroethylene reactor and reacted at 180 °C for 12 h at a heating rate of 2 °C / min;

[0075] (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed three times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 60 °C for 10 h to obtain nanoparticles of CuCo2S4 (p-CuCo2S4).

[0076] Example 4

[0077] This embodiment provides a method for preparing nano-microspherical CuCo2S4, comprising the following steps:

[0078] (1) Add 0.5 mmol of copper acetate hydrate (Cu(CO2CH3)2·xH2O) to 60 mL of ethylene glycol solution and stir until completely dissolved; then add 1 mmol of cobalt acetate hydrate (Co(CO2CH3)2·4H2O) and 3 mmol of thiourea in sequence;

[0079] (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a polytetrafluoroethylene reactor and reacted at 180 °C for 12 h at a heating rate of 2 °C / min;

[0080] (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed three times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 60 °C for 10 h to obtain nano-microspherical CuCo2S4 (m-CuCo2S4).

[0081] The XRD patterns of the nano-flower-like CuCo2S4, nano-sheet-like CuCo2S4, nano-particle-like CuCo2S4 and nano-microsphere-like CuCo2S4 prepared in Examples 1-4 are as follows: Figure 5 As shown in the SEM images Figure 6 、 7 As shown, the N2 adsorption isotherm diagram is as follows Figure 8 As shown in the figure, the electrochemical performance test of CuCo2S4 with different morphologies is shown in the figure Figure 9 shown.

[0082] The specific surface areas of CuCo2S4 with different morphologies are shown in Table 1;

[0083] Table 1 Specific surface area of ​​CuCo2S4 with different morphologies

[0084]

[0085] Example 5

[0086] This embodiment provides a precursor-guided method for preparing CuCo2S4 counter electrodes with different morphologies, comprising the following steps:

[0087] 1) The prepared nanoflower-like CuCo2S4, nanosheet-like CuCo2S4, nanoparticle-like CuCo2S4, and nano-microsphere-like CuCo2S4 powders, ethyl cellulose, and turpentine alcohol were mixed in a mass ratio of 10:1:40, anhydrous ethanol was added, and the mixture was ground into a slurry. The ratio of CuCo2S4 powder to anhydrous ethanol was (0.1-0.2) g: (5-10) mL;

[0088] 2) The slurry was evenly coated on the pre-treated FTO conductive glass surface by screen printing;

[0089] 3) After pre-drying at 80 ℃ for 5 min and high-temperature annealing at 400 ℃ for 30 min, a dense and well-adhesive CuCo2S4 electrode film was formed.

[0090] The electrochemical performance parameters of CuCo2S4 counter electrodes with different morphologies are shown in Table 2:

[0091] Table 2 Electrochemical performance parameters of electrodes with different morphologies

[0092]

[0093] Device assembly and performance testing:

[0094] 1) Construction of FTO / TiO2 / CdS / CdSe / ZnS quantum dot-sensitized photoanode;

[0095] 2) Preparation of polysulfide electrolyte (S 2- / S n 2- );

[0096] 3) Using the CuCo2S4 with different morphologies prepared above as the counter electrode, a "sandwich" QDSSC device was assembled with the photoanode. Electrochemical performance tests such as EIS impedance spectroscopy, Tafel polarization curves, and cyclic voltammetry (CV) were performed, as well as photovoltaic performance tests such as current density-voltage (JV) curves, open circuit voltage decay curves (OCVD), and device on-off (It) curves. The electrochemical performance characterization tests were based on symmetrical cells (both the anode and cathode were counter electrodes) under dark conditions, while the photovoltaic performance tests were conducted under AM1.5G, 100 mW / cm 2 The experiment was carried out based on a "sandwich" type QDSSC device under simulated sunlight conditions.

[0097] like Figure 10 As shown, the working principle of QDSSCs can be divided into the following steps:

[0098] (1) Charge separation

[0099] In QDSSCs, when exposed to light, quantum dots, as light-absorbing materials, generate electron-hole pairs at the interface, also known as the charge separation process, as shown in Equation 1:

[0100]

[0101] (2) Electron injection

[0102] In the second step, the photogenerated electrons from the quantum dots (electron donors) are transferred to the semiconducting metal oxide (electron acceptor, mostly TiO2), while the photogenerated holes are transferred to the electrolyte or CEs. Here, CEs can be metal or semiconductor electrodes (Au, Pt, Cu2S, etc.) with excellent catalytic activity for the redox electrolyte that receives the photogenerated holes from the QDs. At the same time, the electrons in the metal oxide move to the transparent conductive oxide (TCO) substrate and CEs in sequence, as shown in Equations 2, 3, and 4:

[0103]

[0104]

[0105]

[0106] (3) Hole injection

[0107] The electrolyte usually contains a reversible redox couple. When QDSSCs are in operation, S n 2- / S 2- Reducing species S 2- It usually consumes the photogenerated holes accumulated at the TiO2 / QDs interface and efficiently promotes the regeneration of QDs, as shown in the process described by Equations 5 and 6:

[0108]

[0109]

[0110] (4) Diffusion of electrolytes

[0111] Finally, the oxidized S in the electrolyte n 2- The material is easily converted into S by collecting electrons at the CE / electrolyte interface. 2- , which is usually called the redox reaction or diffusion process of the electrolyte, as shown in Equation 7:

[0112]

[0113] In summary, after the above stages, the battery is in its initial state, with no changes to its internal environment. This allows electrons to circulate through the battery multiple times, or even theoretically indefinitely. Therefore, the performance of QDSSCs depends largely on the close coordination of its various components. Furthermore, during QDSSC operation, other non-ideal reactions, known as electron-hole recombination processes, occur. This phenomenon is detrimental to the application of QDSSCs because it can reduce the overall performance of the battery. Therefore, exploring low-cost, efficient, and stable CE materials and effectively modifying the remaining components of QDSSCs are crucial to improving battery performance.

[0114] The JV curves of QDSSCs with CuCo2S4 counter electrodes of different morphologies prepared in Example 5 are shown in Figure 5. Figure 11 As shown in the figure, the QDSSCs constructed with electrodes of different morphologies have a power density of 100 mW cm -2The photovoltaic performance parameters under AM 1.5 G simulated sunlight are shown in Table 3. The cyclic voltammetry (CV) test curves of different morphologies of counter electrodes in the three-electrode system are shown in Figure 12 As shown in the figure, the continuous multi-cycle voltammetry test curves of CuCo2S4 counter electrodes with different morphologies based on symmetrical batteries are shown in the figure. Figure 13 As shown in Figure 2, the open circuit voltage decay (OCVD) curves and on-off experimental test curves of QDSSCs constructed with electrodes of different morphologies are shown in Figure 2. Figure 14 As shown; the efficiency of QDSSCs batteries constructed with electrodes of different morphologies was statistically analyzed. Each battery was grouped with 20 samples. The histogram of the efficiency statistical results is shown in Figure 15 The flower-like CuCo2S4 material (f-CuCo2S4) exhibits significantly improved electrocatalytic performance, exhibiting the largest specific surface area and charge transfer efficiency. The corresponding QDSSC device achieves a power conversion efficiency (PCE) of 7.42%, which is 24–55% higher than the PCE of QDSSCs assembled with CuCo2S4 counter electrodes of other morphologies. It also exceeds the highest conversion efficiency (5.28%) of existing CdS / CdSe-sensitized QDSSCs based on CuCo2S4 counter electrodes by approximately 40%.

[0115] Table 3 Photovoltaic performance parameters of QDSSCs constructed with counter electrodes of different morphologies

[0116]

Claims

1. A precursor-guided method for preparing CuCo2S4 with different morphologies, characterized by: The following steps are involved: (1) Add a certain amount of copper salt to ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt salt and a certain amount of thiourea in sequence; wherein the acid radical ions of the copper salt and the cobalt salt are the same; and the molar ratio of copper ion, cobalt ion and thiourea is 1:(2-3):(5-6); (2) After continuous stirring for a certain period of time, the mixed solution was transferred to a reactor and heated to 160-180 °C for 10-12 h at a heating rate of 2 °C / min; (3) After the above reaction is completed and cooled naturally to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain CuCo2S4 with a certain morphology.

2. The method for preparing CuCo2S4 with different morphologies guided by a precursor according to claim 1, characterized in that: The copper salt described in step (1) is one of copper chloride, copper nitrate, copper sulfate, copper acetate, copper chloride hydrate, copper nitrate hydrate, copper sulfate hydrate, and copper acetate hydrate; the cobalt salt is one of cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt chloride hydrate, cobalt nitrate hydrate, cobalt sulfate hydrate, and cobalt acetate hydrate.

3. The method for preparing CuCo2S4 with different morphologies guided by a precursor according to claim 1, characterized in that: The stirring time in step (2) is more than 30 min.

4. The preparation method according to any one of claims 1 to 3, characterized in that: Nano-flower-shaped CuCo2S4, nano-sheet-shaped CuCo2S4, nano-particle-shaped CuCo2S4 or nano-microsphere-shaped CuCo2S4 can be prepared.

5. A method for preparing nanoflower-like CuCo2S4, characterized by: The following steps are involved: (1) Add a certain amount of copper chloride or copper chloride hydrate to ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt chloride or cobalt chloride hydrate and a certain amount of thiourea in sequence; the molar ratio of the added copper ions, cobalt ions and thiourea is 1:(2-3):(5-6); (2) Continue stirring for more than 30 min, transfer the mixed solution to a reactor, and heat it to 160-180 °C for 10-12 h at a heating rate of 2 °C / min; (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain nanoflower-like CuCo2S4.

6. A method for preparing nano-sheet CuCo2S4, characterized in that: The following steps are involved: (1) Add a certain amount of copper nitrate or copper nitrate hydrate to an ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt nitrate or cobalt nitrate hydrate and a certain amount of thiourea in sequence; the molar ratio of the added copper ion, cobalt ion and thiourea is 1:(2-3):(5-6); (2) Continue stirring for more than 30 min, transfer the mixed solution to a reactor, and heat it to 160-180 °C for 10-12 h at a heating rate of 2 °C / min; (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol, respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain nanosheet-shaped CuCo2S4.

7. A method for preparing nanoparticle-shaped CuCo2S4, characterized by: The following steps are involved: (1) Add a certain amount of copper sulfate or copper sulfate hydrate to ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt sulfate or cobalt sulfate hydrate and a certain amount of thiourea in sequence; the molar ratio of the added copper ions, cobalt ions and thiourea is 1:(2-3):(5-6); (2) Continue stirring for more than 30 min, transfer the mixed solution to a reactor, and heat it to 160-180 °C for 10-12 h at a heating rate of 2 °C / min; (3) After the above reaction is completed and naturally cooled to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol, respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain nanoparticles of CuCo2S4.

8. A method for preparing nano-microspherical CuCo2S4, characterized by: The following steps are involved: (1) Add a certain amount of copper acetate or copper acetate hydrate to an ethylene glycol solution and stir until completely dissolved; then add a certain amount of cobalt acetate or cobalt acetate hydrate and a certain amount of thiourea in sequence; the molar ratio of the added copper ions, cobalt ions and thiourea is 1:(2-3):(5-6); (2) Continue stirring for more than 30 min, transfer the mixed solution to a reactor, and heat it to 160-180 °C for 10-12 h at a heating rate of 2 °C / min; (3) After the above reaction is completed and cooled naturally to room temperature, the resulting precipitate is washed several times with deionized water and anhydrous ethanol, respectively, and then placed in an oven at 50-60 °C for 10-15 h to obtain nano-microspherical CuCo2S4.

9. CuCo2S4 prepared by the preparation method according to any one of claims 1 to 3 or the preparation method according to any one of claims 5 to 8 is used to prepare a counter electrode of a QDSSC device.

10. A method for preparing precursor-guided CuCo2S4 counter electrodes with different morphologies, comprising the following steps: 1) CuCo2S4 powder of a certain morphology is mixed with a pore-forming agent and a binder in a mass ratio of 10:(1-2):(40-50), a dispersant is added in a ratio of 0.1-0.2 g of CuCo2S4 powder to 5-10 mL of dispersant, and the mixture is ground into a slurry; the CuCo2S4 powder is prepared by the preparation method of any one of claims 1-3 or the preparation method of any one of claims 5-8; 2) The slurry was evenly coated on the pre-treated FTO conductive glass surface by screen printing; 3) After pre-drying at 80 °C for 3-5 min and high-temperature annealing at 350-400 °C for 30-35 min, a dense and well-adhesive CuCo2S4 electrode film is formed.